Diseño y simulación de una mezcladora-amasadora para preparar 12 KG/H de pasta alimenticia. - Renjifo Mera, Carlos Alejandro (2018)
The handmade processing of pasta presents disadvantages in factors such as homogeneity, effort and time of preparation. At present, there are machines capable of performing this work in a relatively short time, the problem is that these machines are not commercially available in Ecuador; so that in order to obtain them, it should be imported from abroad. This would increase approximately 30% to 50% more of its commercial value, due to import costs and tariffs. The present work is focused in giving a design solution for the elaboration of a machine capable of carrying out 12 Kg/h of alimentary dough considering the processes of mixing-kneading and extruded. The mixing and extrusion shafts, will be subjected to radial and axial loads, for which the safety factor is determined that ensures that the diameters of the shafts do not fail under static loads or fatigue. The values of the fatigue safety factor, calculated analytically, will be 2.04 for the mixing shaft and 2.5 for the extrusion shaft. The simulation carried out in SolidWorks, of the mixing and extruded shafts, provides a static design safety factor of 2.21 and 3.18 respectively. This guarantees that the design has been correctly carried out. The financial analysis shows that the most representative cost in the construction of the machine corresponds to the two engines, which represent approximately 41% of the total cost; Furthermore, will be shown that the initial investment will be recovered in a time of two months, since with this machine you can double the production of pasta inside a commercial establishment.